From European war to Church union: Ivan the Terrible, Stephen Báthory, and Antonio Possevino - K. Yu. Erusalimskii (Шаги, 2023)
The epistolary polemic between Stephen Báthory and Ivan the Terrible unfolded in 1576–1578 and reached its climax in 1579–1581. It ended through the mediation of the Holy See. The Jesuit Antonio Possevino’s mission to the Polish-Lithuanian Commonwealth and Russia left a lasting imprint on diplomatic correspondence and negotiations, opening new perspectives for both parties as well as for the Holy See against the background of plans for a union of Churches and for confronting the Reformation and the Turkish threat to Christian states. The article clarifies the conclusions of previous studies on the course of the negotiations and shifts the emphasis from the projects of the Roman See to a multilateral lens. This allows us to reconsider the positions of the three main participants, which changed during the peacemaking mission. The main attention is paid to Ivan the Terrible’s letter to the Polish king of June 29, 1581, Stephen Báthory’s reply of August 2, 1581, prepared with the assistance of the Crown and the Lithuanian chanceries, and Ivan the Terrible’s ‘speeches’ (posolskiie rechi) delivered in Staritsa on September 12, 1581. These extensive ‘speeches’ concluded the “hot” epistolary and oral phase of Ivan the Terrible’s war with Stephen Báthory, but they were merely an opening for Antonio Possevino’s efforts to realize the Holy See’s aims.